Insight into the Pore Structures and Its Impacts on Movable Fluid in Tight Sandstones - Dazhong Ren; Fu Yang; Rongxi Li; Desheng Zhou; Dengke Liu; Ying Li (Geofluids)
Both the characteristics of pore structure and movable fluid are significant properties in controlling the flow regularity in pores in tight sandstones. However, the governing factors that affect the fluid flow features will still be a myth. In our research, the western area of the Sulige gas field was chosen as the research region, and various kinds of experiments were conducted. Three reservoir groups, including intergranular-dissolved pore type, dissolved-intercrystalline pore type, and pore plus microcracks type were identified on the basis of pore development features. The results suggest that the intergranular-dissolved pore type has a more prominent influence on the high movable fluid saturation and larger pores. Both large throat sizes and homogeneous pore-throat degree demonstrate high movable fluid saturation. The increment of the thickness of water-film resulted from hydrophilic enhancement, indicating that an increased hydrophilic will decrease the movable fluid saturation and block the throats. The reservoirs of different pore combination types are closely related to the gas content of the reservoir.